Chinese character card game: learners’ attitudes and motivation / Ting Hie-Ling - Ting, Hie-Ling (2021)
Chinese character recognition is the first step to learn Chinese characters. However, due to the complexity structure of Chinese characters, learners often show unsatisfactory result in their Chinese character recognition. As a result, this can affect Mandarin learners to further their understanding in Mandarin language learning. Numerous researches proven that educational game help in learning process and it is essential to adopt in this millennial era. Due to that, an innovative teaching and learning card game, Chinese Character Battle (CCB, 汉字对决)which may give a great impact on learners’ performance in Chinese characters learning was designed and implemented in Mandarin language classroom. This card game is suitable for Mandarin learners from different level of proficiency. The CCB provided plethora of advantage for native-Mandarin learners and non-native Mandarin learners in their learning of Chinese characters. As for its novelties, CCB equipped with the knowledge that learners need to acquire in learning Chinese characters and reinforce learners’ memories on each Chinese character through visualization of each character. This card game is recommended for Mandarin teacher and Mandarin learners as it offer a fun and engaging learning environment. This study was carried out to explore the attitudes and motivation of learners in using CCB as a Chinese character learning tool. The findings from the survey revealed the positive attitudes and high level of motivation among students in using CCB. Most of participants agreed that CCB gave them a lot of benefits. They also responded that CCB is useful and effective learning tool for them to learn and improve their performance on learning Chinese Characters.